Kesamaan Bunyi pada Sajak (Kajian Fonologi al-Qur’an dalam Surat al ‘Asar) - Amrulloh, Muhammad Afif (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2017)
Abstract: The existence of the verse in the Qur'an are reflected through the similarity of the sound at each end of the paragraph that included part of the beauty of the Qur'an. The beauty of the Qur'an not only on the aspects of sound, but also on aspects of writing. Therefore conducted the study of beauty lafazh on phonology, namely rhyme. Using the research library or library research, the data obtained based on the literature. The data presented and analyzed systematically. Surat al-‘asra becomes the object of the material. Based on the results of research that the paragraph on how the letter showed the same pattern of verse in the form of the sound of the consonants as well as vocals. The letters or the same vocal found a total of 11 vocal /a/ , vocal sound with five /u/, and three vocal sound of/i/. Most patterns of vocal it is located at the end of paragraph or the end of a Word using the same vocal sound that is /i/. Whereas the same vocal sound at the end of the word in the form of sound /u/. As for the pattern of most consonants is found in the same consonant /r/ that is numbered six the same consonant pattern and other form of consonant /l/ there are three consonants. While the consonant /w/,/s/,/t/,/m/,/' a/ as much as two consonants. The identification of similarities that sound more and give space to the existence of balaghah and aswat are important and can not be separated in the study of al-Qu'an. Keywords:: fonologi, sajak, bunyi